The Scientific Cooperation Model of the Musculoskeletal Sections of the National Belgian and Dutch Societies of Radiology - Vanhoenacker, Filip M.; Van der Woude, Henk-Jan; Reijnierse, Monique (Seminars in Musculoskeletal Radiology, 2025)
This history page is dedicated to the history of the Musculoskeletal Sections of the Belgian Society of Radiology and the Dutch Society of Radiology that take part in the continuing education of musculoskeletal radiology in their respective countries. Since 2008, these societies have worked together and organized a joint annual meeting dedicated to the field of musculoskeletal radiology.
Keywords: Belgian Society of Radiology; Dutch Society of Radiology; musculoskeletal; history